The virtual banking revolution : the customer, the bank and the future - Essinger, James, 1957- (London : International Thomson Business Press, 1999)
The virtual banking revolution. Setting the virtual banking revolution in its strategic context. The origins and competitive implications of the virtual banking revolution. The cost issue...
Keywords: Finance; Economics; Banks; Financial services industry -- Great Britain -- Automation; Banks and banking -- Great Britain -- Automation